2017
DOI: 10.3892/ol.2017.5717
|View full text |Cite
|
Sign up to set email alerts
|

Optimized construction of MUC1-VNTRn DNA vaccine and its anti-pancreatic cancer efficacy

Abstract: Considering mucin 1-variable number tandem repeat (MUC1-VNTRn) as a novel target for pancreatic cancer immunotherapy, the present study aimed to screen and identify the pVAX1-MUC1-VNTRn DNA vaccine with the strongest immunogenicity. Following construction of a pVAX1-MUC1-VNTRn plasmid, immature dendritic cells (DCs) were subjected to transfection, and mature DCs were then co-cultured with autologous T-cells. The numbers of cytotoxic T lymphocytes (CTLs) secreting interferon (IFN)-γ were determined using an enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…A variety of MUC1 DNA vaccines have been developed to date. Studies have confirmed that the MUC1 DNA vaccine induces a specific immune response against MUC1, produces an obvious tumour suppression effect and prolongs patient survival time (85)(86)(87). In phase I/II clinical trials, MUC1-loaded DC vaccines in the combination therapy of patients with advanced pancreatic cancer enhanced the disease suppression rate and effectively extended the survival period (88,89).…”
Section: Progress and Perspectivesmentioning
confidence: 91%
“…A variety of MUC1 DNA vaccines have been developed to date. Studies have confirmed that the MUC1 DNA vaccine induces a specific immune response against MUC1, produces an obvious tumour suppression effect and prolongs patient survival time (85)(86)(87). In phase I/II clinical trials, MUC1-loaded DC vaccines in the combination therapy of patients with advanced pancreatic cancer enhanced the disease suppression rate and effectively extended the survival period (88,89).…”
Section: Progress and Perspectivesmentioning
confidence: 91%
“…These antigens can be used to sensitize dendritic cells, which subsequently cause an immune response from CD4+ lymphocytes [ 63 ]. MUC-1 peptide is also able to determine an antitumor immune response mediated by dendritic cells in patients with metastatic pancreatic cancer [ 64 ].…”
Section: Vaccines In Digestive Tract Cancersmentioning
confidence: 99%
“…Four out of twelve (33.3%) patients who received this MUC-1-based tumor vaccine were alive after four years without evidence of recurrence[ 106 ]. An optimized construct with MUC-1-variable number tandem repeats has been designed with much more potent immunogenicity[ 107 ].…”
Section: Immunotherapy In Pancreatic Cancermentioning
confidence: 99%